Universality and Modern Individuality Civilization Paradigm in The Field of Human Rights: Dialogue vs Conflict. - Гнатюк, Тетяна Миколаївна; Карвацька, Світлана Богданівна; Заморська, Любов; Чепель, Ольга Дмитрівна; Продан, Ірина (Європейський центр сталого розвитку, 2021)
Thearticlegivesreasontosay,thatthekeypointofglobalizationinthefieldofhumanrightsistheuniversalizationofthisarea.Theuniversalizationofhumanrightsisakeytrend,butnottheonly,intheirdevelopment.Humanrightsasuniversalmoralprinciplesspecificationaretherulesonwhichpeacefulcoexistenceofindividualsanddifferentculturesintermsofglobalproblemsispossible.Suchanapproachallowstosolvetheseeminglyirreconcilablecontradictionbetweenthepositionsoftheuniversalismofhumanrightsandculturalidentitypluralism:therighttoculturalidentityisasignificantindividualright.ThereshouldbeacriticalapproachtothethesisoftheinsurmountablefundamentalityofculturaldifferencesbetweenEasternandWesterncultures.ItisnecessarytodistinguishbetweensituationsofimposingWesternstandardsonotherculturesandtherealimportanceanduniversalityofhumanrightsforthemodernworld.Culturaldiversityshouldneverbeusedasanexcuseforchauvinisticnationalism.Itisinterculturaldialoguesthatshouldfacilitatefruitfulexchangesofideasonhumanrightsissuesintheperspectiveofculturaldiversityandbecomethebasisfortheformationofadialogicalcivilization.Contemporaryhumanrightsdiscoursehastotakeplaceinthecontextofaglobalworldorderemergencethroughthejuxtapositionofconceptssuchasuniversality,culturaldiversityandculturaldialogue
Keywords: globalization; human rights sphere; legal standards; dialogical civilization; intercultura ldialogue